The Development Prospect Of Households For Coconut Cooking Oil In Galang Sub-District, Deli Serdang Regency - Pinem, Nurul Fajriah; Nasution, Delima Lailan Sari; Pohan, Annisa Rizkia (Talenta Publisher Universitas Sumatera Utara, 2021)
Micro, small and medium enterprises (MSMEs) in Indonesia have a very large and important contribution to the country's economy. MSMEs currently running in the community consist of many fields, one of which is the use of Indonesian agricultural products. Coconut oil can be used as cooking oil, margarine and white butter, a component in soap making and cosmetic formulations. MSMEs making coconut oil have quite a large business opportunity, one of which is the Maida Coconut Cooking Oil Business which is located in Galang District, Deli Serdang Regency. The amount of coconut oil produced is still on a small scale. This is due to very simple equipment, high selling prices, and limited range of marketing strategies. This activity aims to help Maida MSMEs to increase production by providing assistance in the form of equipment and determining the proper cost of goods sold. The results showed that the cost of goods sold obtained before adding tools based on the full costing method was IDR 41,746/L and variable costing was IDR 39,236/L. Meanwhile, after adding equipment based on the full costing method it is IDR 104,211/L and variable costing is IDR 89,757/L.